2020
DOI: 10.1007/s00423-020-01907-x
|View full text |Cite|
|
Sign up to set email alerts
|

Volume, outcomes, and quality standards in thyroid surgery: an evidence-based analysis—European Society of Endocrine Surgeons (ESES) positional statement

Abstract: Introduction Continuous efforts in surgical speciality aim to improve outcome. Therefore, correlation of volume and outcome, developing subspecialization, and identification of reliable parameters to identify and measure quality in surgery gain increasing attention in the surgical community as well as in public health care systems, and by health care providers. The need to investigate these correlations in the area of endocrine surgery was identified by ESES, and thyroid surgery was chosen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 62 publications
0
47
0
Order By: Relevance
“…A recent positional statement by the European Society of Endocrine Surgeons also concluded that a surgeon volume-outcome effect exists for thyroid surgery [ 20 ]. They identify > 50 procedures per annum per surgeon as an appropriate threshold for high volume and < 25 procedures per annum per surgeon as an appropriate threshold for low volume.…”
Section: Discussionmentioning
confidence: 99%
“…A recent positional statement by the European Society of Endocrine Surgeons also concluded that a surgeon volume-outcome effect exists for thyroid surgery [ 20 ]. They identify > 50 procedures per annum per surgeon as an appropriate threshold for high volume and < 25 procedures per annum per surgeon as an appropriate threshold for low volume.…”
Section: Discussionmentioning
confidence: 99%
“…We included both prospective and retrospective studies; the included studies cannot control for various confounders that may affect the outcomes, including the original thyroid disease, the patient's age, comorbidities, and the extent of surgery, including central lymph nodes dissection [ 27 ]. Besides, a high-volume surgical team might affect the outcomes [ 28 ]. Also, the limitations include the significant observed heterogeneity and studies published only in the English language.…”
Section: Discussionmentioning
confidence: 99%
“…In part this may be caused by the increasing use of technology aimed to improve outcomes. The morbidity after thyroid surgery is low when performed by high-volume surgeons [ 50 , 51 ] and the real-world results suggest a gross underreporting of surgical morbidity [ 52 ]. Hypoparathyroidism, recurrent laryngeal nerve palsy, and post-operative haemorrhage reduce QoL and add cost to the overall treatment of thyroid cancer [ 52 ].…”
Section: Surgical Technology: a Cost-effective Addition?mentioning
confidence: 99%